Diversity of Parrotfish at Fishing Port, Kendari City, Southeast Sulawesi - Fekri, Latifa; Asriyana, Asriyana; Subhan, Subhan; Disnawati, Disnawati; Hatma, Muhammad Iksan (Politeknik Kelautan dan Perikanan Karawang, 2023)
Parrotfish are included in the group of herbivore fish which have an important role in aquatic ecosystems, especially in the maintenance of coral reefs. This study aimed to determine the diversity of parrotfish species in the Sodoha Fishing Port (TPI), Kendari City, Southeast Sulawesi. Identification of parrotfish species by Kuiter and Tonozuka, White, and Fishbase. The results of identification showed six species of parrotfish were obtained, namely Chlorurus microrhinos (Bleeker, 1854), C. bleekeri (Deeufort, 1940), C. strongylocephalus (Bleeker, 1855), Scarus rivulatus (Valenciennes, 1840), S. niger (Forsskål, 1775), dan S. chameleon (Choat & Randall, 1986). Utilization of parrot fish resources continues to increase by> 40% annually. Sustainable management of parrotfish is needed for the quality of the aquatic environment, especially coral reefs and the sustainability of their utilization.